2018
DOI: 10.3390/mi9120647
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the Electrokinetic Equations for Multi-ionic Electrolytes Including Different Ionic Size Related Effects

Abstract: One of the main assumptions of the standard electrokinetic model is that ions behave as point-like entities. In a previous work (López-García, et al., 2015) we removed this assumption and analyzed the influence of finite ionic size on the dielectric and electrokinetic properties of colloidal suspensions using both the Bikerman and the Carnahan–Starling equations for the steric interactions. It was shown that these interactions improved upon the standard model predictions so that the surface potential, electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The table generally shows decreased surface potential with decreased pH, which is consistent with Fig. 2 of the research work of López et al, (2018).The increased positive surface potential of mica after pH of 3.43 shows increased protonation of surface functional groups leading to the development and increase surface positive potential.…”
Section: Discussionsupporting
confidence: 87%
“…The table generally shows decreased surface potential with decreased pH, which is consistent with Fig. 2 of the research work of López et al, (2018).The increased positive surface potential of mica after pH of 3.43 shows increased protonation of surface functional groups leading to the development and increase surface positive potential.…”
Section: Discussionsupporting
confidence: 87%
“…Here, to calculate (hs) i γ we will use the expression for the activity coefficient of a hard-sphere fluid composed of several components of different radii. This expression, which is derived from the BMCSL equation of state [12,13], reads [14]:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Alargova et al [8,9] and Srinivasan and Blankschtein [10] demonstrated that the effect of counterion binding has to be taken into account in order to achieve agreement between theory and experiment, especially in the case of multivalent counterions. Koroleva and Victorov [11] took into account the effect of the finite size of the ions by using the Boublik−Mansoori−Carnahan−Starling−Leland (BMCSL) equation for a mixture of hard spheres of different radii [12][13][14]. Note, however, that all these studies are still using some of the simplifying assumptions adopted in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of finite ionic size on the dielectric and electrokinetic properties of colloidal suspensions is analyzed by López-García et al [6]. They extended previous works to systems made of three or more ionic species with different ionic sizes and found qualitative and quantitative differences with respect to the standard electrokinetic model.…”
mentioning
confidence: 99%